Expert System Diagnose Disease Persian cat with Bayes Theorem Method - Yustrida Yanti; Sulindawaty Sulindawaty (Journal of Computer Networks, Architecture and High Performance Computing, 2020)
Lack of knowledge of the disease and the limitations Pesia cat disease management is often experienced by the owners of Persian cats. Therefore it is necessary to act / respond quickly to prevent infection with the disease more serius.Teorema Bayes is a method used to predict the probability. Therefore, in this study will be analyzed Persian cat disease data using Bayes theorem using four diseases areFeline Leukemia Virus, Worms, Cat Flu and Mushrooms Cryptococus. Based on these descriptions, we need a system that can represent an expert who has the knowledge base and experience of the Persian cat disease, which is an expert system. Developments in information technology more widely and rapidly. So much in use in various fields. That accompanied the information technology internet support each other resulting in increased web-based technologies